In Pursuit of the Person in Psychology (KULT_online, 2019)
Brian Schiff’s new book, entitled A New Narrative for Psychology, takes a critical look at the current identity crisis of psychology, which is marked by a fragmentation into different theoretical perspectives and a lack of shared terminology. Schiff argues that a narrative perspective can lend the discipline a new self-conception and common direction. Centering research around narrative and meaning-making processes would help the discipline to dispose of issues like the convention of relying on quantitative research and the misinterpretation of findings. Taking a functionalist approach to narrative, the book reformulates the conception of narrative psychology to offer a new way to do psychological research. It is an appeal to the discipline to consider alternative practices and to focus on the particular, rather than the general. By doing this, the book constitutes an important contribution to the debate on contemporary psychology’s future.